The Relationship Between Nutritional Status With The Growth And Development Of Toddlers 1-3 Years In Pratama Bunda Patimah Clinic - Artikan Fitrin Ndraha; Rotua Lenawati Tindaon; Teguh Juwita Marito Napitupulu (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Nutritional status is the result of a balance with food intake and the need for nutrients in the human body. Nutritional status is influenced by diet and the ability of these nutrient levels in the process of maintaining normal metabolic integrity. This research method uses descriptive analytic. The population in this study were all toddlers 1-3 years. The research sample used the total population technique. Data collection uses Primary and Secondary data. The data analysis technique uses the chi-square test. The results obtained from data analysis using the chi-square test showed that out of 25 respondents (75.7%) with good nutritional status with good growth, 24 respondents (72.7%) had good nutritional status with poor growth, 1 respondent (3, 0%) from the results of the chi-square test showed a significant value, the p-value was 0.007 <0.05, so it was concluded that there was a relationship between nutritional status and growth. Of the 33 respondents, it was shown that out of 25 respondents (75.8%) good nutritional status with appropriate progress was 25 respondents (75.8%), good nutritional status with doubtful development was 0 respondents (0.0%), good nutritional status with the development of deviations of 0 respondents (0.0%) from the results of the chi-square test showed a significant value obtained p-value was 0.005 <0.05 so it was concluded that there was a relationship between nutritional status and development. It was concluded that there is a relationship between Nutritional Status and the Growth and Development of Toddlers 1-3 Years at the Bunda Patimah Primary Clinic in 2022. It is recommended for places and health workers to increase monitoring of nutritional status, growth and development of children, carry out routine early detection of irregularities in child growth and development.